Necrotrophic behaviour of Erwinia amylovora in apple and tobacco leaf tissue. (9th November 2016) - Sobiczewski, P.; Iakimova, E. T.; Mikiciński, A.; Węgrzynowicz‐Lesiak, E.; Dyki, B.
Abstract : An important issue related to the epidemiology of fire blight, a devastating disease of apples and pears, is how its causal agent, the bacterium Erwinia amylovora, survives and disseminates in the environment. Almost no information is available on the possibility of this pathogen overwintering as a necrotroph. In this study, bacterial survival in dead apple and tobacco (a non‐host) leaf tissues was addressed. In necrotized leaves collected 5, 6, 7 and 8 months following shoot inoculation of apple trees, viable E. amylovora cells were present in over 50% of samples from the midrib and in over 10% of samples from lateral veins, but were never found in parenchyma. Using a PCR‐based method, pathogen DNA was detected in more than 50% of samples that were found to be free of viable cells by conventional plating out. However, PCR analysis was insufficient to distinguish between the DNA of viable and dead bacteria. Sugars appropriate for bacterial growth were found in dead apple leaves. In spot‐inoculated attached apple and tobacco leaves, a remarkable increase in the bacterial population was observed in lesions that developed as a hypersensitive response (HR). As in other necrotrophic interactions, bacterial proliferation was associated with massive hydrogen peroxide production and progression toward plant cell death. The results indicate that E. amylovora has an ability to survive as a semi‐necrotroph or necrotroph, which allows for overwintering in dead apple leaves.